Refeeding partially reverses impaired fracture callus in undernourished rats - Botega, Iara I.; Guedes, Patrícia M. S. G.; Ximenez, João Paulo B.; Zamarioli, Ariane; Volpon, José B. (Frontiers in Endocrinology, 2024)
Background Adequate nutritional intake plays a crucial role in maximizing skeletal acquisition. The specific effects of a general food restriction and refeeding on fracture healing are yet to be fully understood. The aim of this study was to assess the impact of general food restriction and refeeding on fracture repair. Methods Fifty-four male Wistar Hannover rats were randomly assigned into three groups: (1) Sham: Sham rats with femoral fracture; (2) FRes: Food-restricted rats with fracture, (3) Fres+Ref: Fres rats with refeeding. Following weaning, the FRes and Fres+Ref groups received 50% of the food amount provided to the Shams. In the sixth week of the experiment, all animals underwent a mid-right femur bone fracture, which was subsequently surgically stabilized. Following the fracture, the Fres+Ref group was refed, while the other groups maintained their pre-fracture diet. Bone calluses were analyzed on the fifth-day post-fracture by gene expression and on the sixth-week post-fracture using dual-energy X-ray absorptiometry, morphometry, histomorphometry, immunohistochemistry, computed microtomography, and torsion mechanical testing. Statistical significance was determined at a probability level of less than 0.05, and comparisons were made using the ANOVA test. Results Food restriction resulted in significant phenotypic changes in bone calluses when compared to sham rats characterized by deterioration in microstructure (i.e., BV, BV/TV, Tb.N, and Conn.D) reduced collagen deposition, bone mineral density, and mechanical strength (i.e., torque at failure, energy, and stiffness). Moreover, a higher rate of immature bone indicated a decrease in bone callus quality. Refeeding stimulated bone callus collagen formation, reduced local resorption, and effectively restored the microstructural (i.e., SMI, BCa.BV/TV, Tb.Sp, Tb.N, and Conn.D) and mechanical changes (i.e., torque at failure, energy, and angular displacement at failure) caused by food restriction. Despite these positive effects, the density of the bone callus, collagen deposition, and OPG expression remained lower when compared to the shams. Gene expression analysis didn’t evidence any significant differences among the groups. Conclusions Food restriction had detrimental effects on osseous healing, which was partially improved by refeeding. Based on these findings, new research can be developed to create targeted nutritional strategies to treat and improve fracture healing.